Estado nutricional, anemia e fatores de risco cardiometabólico em adultos e idosos quilombolas de Goiás - Santos, Renata Carvalho dos (2016)
Quilombolas communities are ethnic group defined by self-definition criteria and presumption of black ancestry. There are few studies and data about health of these subjects, and between available study highlight higher prevalence of overweight and related diseases. However, national survey data also show that anemia and malnutrition are prevalent among black women and children. Nevertheless, lacking most comprehensive studies to understand the health profile of quilombo population from Brazil. The objective of this research was to evaluate nutritional status, anemia frequency and cardiometabolic risk factors in adults and elderly from quilombolas communities of Goias state/Brazil. We carried out an analytical cross-sectional study with 287 subjects. Were performed anthropometric measurements (weight, height, waist circumference, and calculated BMI and Waist to height ratio - WHtR) blood tests (complete blood count, serum ferritin, fasting glucose and lipid profile), and socioeconomic and demographic questionnaire. The first article discussed the rate of anemia and iron deficiency and its relationship to overweight. Frequency of anemia and iron deficiency was low (5,9% and 4,7% respectively) and wasn’t association with overweight. Women had higher overweight than men, and men had higher underweight. BMI was higher in urban communities and in adults. Hemoglobin was lower in urban communities (p<0,05). The correlation indicated that increasing BMI is accompanied by decreases in hemoglobin and ferritin. RBC indices indicated 10,9% of microcytosis and 9,4% of anisocytosis. The second article discusses the assessment of nutritional status and association with cardiometabolic risk factors. Participants presented 54,4% of overweight and 67,9% higher waist-to-height ratio. The group with overweight differs from the eutrophic group in relation to HDL, VLDL, TG, leukocytes, lymphocytes, and platelets. And 15.2% of the population had three or more metabolic risk factors, moreover, in this group, leukocytes and lymphocytes were significantly higher. Women had more metabolic abnormalities than men. In conclusion, the main health problem in these communities refers to overweight and related diseases. Metabolic abnormalities increase the risk of developing cardiovascular disease, which are the leading cause of death in Brazil. The low prevalence of anemia and iron deficiency needs to be better investigated together food consumption. It’s must also be investigated genetics anemia, such as thalassemia and sickle cell due the abnormalities found in RBC indices without decreasing hemoglobin and ferritin.